2009
DOI: 10.1111/j.1468-3083.2008.03022.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fixed low‐dose isotretinoin (20 mg, alternate days) with topical clindamycin gel in moderately severe acne vulgaris

Abstract: Six months of treatment with fixed-dose, alternate-day isotretinoin (20 mg) plus topical 1%clindamycin gel was found to be effective in the treatment of moderate acne in adult patients, with a low incidence of side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 19 publications
4
63
0
2
Order By: Relevance
“…An analysis of the studies revealed that there were two broad categories of studies; in one in whom relapse occurred after standard treatment [5,6,16] and the other group where a low dose was given at the outset (daily/alternate day regimen) [4,[7][8][9][10]12,14,15,[17][18][19] [ Tables 1 and 2].…”
Section: Low-dose Isotretinoin Low-dose Isotretinoinmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the studies revealed that there were two broad categories of studies; in one in whom relapse occurred after standard treatment [5,6,16] and the other group where a low dose was given at the outset (daily/alternate day regimen) [4,[7][8][9][10]12,14,15,[17][18][19] [ Tables 1 and 2].…”
Section: Low-dose Isotretinoin Low-dose Isotretinoinmentioning
confidence: 99%
“…[4,[7][8][9]12,14,15,[17][18][19] in various doses, like daily, [7,17,18] intermittent therapy, [4,12,18] alternate day therapy [19] or gradually increasing the daily dose. [5] As there is marked heterogeneity in these regimens, a more logical way is to compare them on the basis of dose per day (mg/kg/day), which ranges from 0.14 mg/ kg/day to 0.75 mg/kg/day.…”
Section: Low-dose Isotretinoin (Regimens)mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] In the recent years however a number of investigators have found it to be useful even in relatively low doses ranging from 0.3 to 0.5 mg/kg/day. [8][9][10][11][12] It has been seen that there is dose dependent decrease in sebum production with oral isotretinoin. 13 Though isotretinoin is effective in acne even in low doses but there are significantly higher chances of relapses and need of retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно резуль-татам работы K. Sardana и соавт. [22], эффективность использования изотретиноина через день в сочета-нии с топическим клиндамицином оказалась равной 87%. Препараты клиндамицина, эритромицина ис-пользуют для уменьшения воспалительных элемен-тов в первые месяцы терапии, также они могут при-меняться как поддерживающая терапия после окон-чания лечения системным изотретиноином.…”
Section: рис 2 больной г через 2 мес от начала терапииunclassified